2016
DOI: 10.1038/mp.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease: modeling an Aβ-centered biological network

Abstract: In genetically complex diseases, the search for missing heritability is focusing on rare variants with large effect. Thanks to next generation sequencing technologies, genome-wide characterization of these variants is now feasible in every individual. However, a lesson from current studies is that collapsing rare variants at the gene level is often insufficient to obtain a statistically significant signal in case-control studies, and that network-based analyses are an attractive complement to classical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 180 publications
2
34
0
Order By: Relevance
“…Since its formulation in the early 1990s, the amyloid hypothesis has been somewhat refined but remains the most influential conceptual framework for AD [58]. Centered on Aβ, Campion et al manually curated a biological network of 335 genes/proteins which have been shown to interfere with Aβ production, clearance, aggregation, or toxicity, including amyloid precursor protein APP , beta-secretase BACE1 , gamma-secretases PSEN1 / PSEN2 , and Aβ clearance proteins like APOE and CLU (reviewed in [59]). Of these 335 genes, 330 were profiled by the current microarray dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Since its formulation in the early 1990s, the amyloid hypothesis has been somewhat refined but remains the most influential conceptual framework for AD [58]. Centered on Aβ, Campion et al manually curated a biological network of 335 genes/proteins which have been shown to interfere with Aβ production, clearance, aggregation, or toxicity, including amyloid precursor protein APP , beta-secretase BACE1 , gamma-secretases PSEN1 / PSEN2 , and Aβ clearance proteins like APOE and CLU (reviewed in [59]). Of these 335 genes, 330 were profiled by the current microarray dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Its aggregation in cerebromeningeal vessels leads to cerebral amyloid angiopathy (CAA), a condition frequently associated with AD and responsible for recurrent haemorrhagic strokes and white matter lesions. PSEN1 and PSEN2 encode the presenilins, which constitute the catalytic subunit of the γ-secretase complex (for review, see [10,11]). AD-EOAD causative mutations are thought to be responsible for the increased aggregation of the Aβ peptide in the brain’s parenchyma through one of the two following mechanisms: increased overall production of all Aβ species (e.g., APP duplications or APP mutations located around the β cleavage site) or production of a more aggregation-prone form of the Aβ peptide.…”
Section: Introductionmentioning
confidence: 99%
“…a combination of factors whose effects are cumulative over a single susceptibility curve [27] . This assumption is in contradiction with current knowledge on AD susceptibility with diverse pathways reported to converge and probably interact towards Aβ toxicity [3] .…”
Section: Introductionmentioning
confidence: 62%
“…According to the amyloid cascade [1] , in AD the killer is Tau, Aβ being the trigger [2] . Note that according to this framework, protein-altering variants of virtually all genes encoding a protein involved in the regulation of APP processing, Aβ secretion, clearance, or toxicity may influence the AD pathophysiological process and therefore be part of the genetic determinism of AD [3] .…”
Section: Introductionmentioning
confidence: 99%